Hubungan Dukungan Suami dengan Pemberian ASI Eksklusif pada Ibu Menyusui di Kabupaten Bulukumba - Husnul Khatimah; Kurniati Akhfar; Arfiani Arfiani; Rahmaniyah. R; Jusni Jusni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Exclusive breastfeeding is very beneficial for reducing child mortality rates and improving maternal health in accordance with one of the goals of the Sustainable Development Goals (SDGs) which ensures that children consume exclusive breast milk, but the achievement of Exclusive Breastfeeding in South Sulawesi Province in 2023 is 74.0%. This figure has not reached the national target in 2023, which is 75%. There are 12 districts/cities that have not reached the target, including Bulukumba Regency with an achievement of 60%. The success rate of exclusive breastfeeding can be successful with the support of husbands to breastfeeding mothers to breastfeed their babies because Exclusive Breastfeeding has very broad benefits, not only for babies, but also for mothers, families, and even the country. This study aims to The Relationship Between Husband Support and Exclusive Breastfeeding in Breastfeeding Mothers in Bulukumba Regency. The method used in this study is quantitative research with a total sample of 13 people selected using the total sampling technique. The results of the study showed that most of the husband's support did not support by not providing exclusive breastfeeding as many as 5 people (38.5%), and most of the husband's group supported by providing exclusive breastfeeding as many as 5 people (38.5%). And there were 3 respondents (23.0) who received support from their husbands but did not provide exclusive breastfeeding. Using the chi-square statistical test, a P-value of 0.04 <0.005 was obtained. Thus, there is a significant relationship between the relationship between husband's support and the provision of exclusive breastfeeding in breastfeeding mothers.